Persistence of Legionella in Routinely Disinfected Heater-Cooler Units and Heater Units assessed by Propidium Monoazide qPCR - Ditommaso, Savina (Pathogens, 2020)
Background: Evidence to date indicates that heater–cooler units (HCUs) and heater units (HUs) can generate potentially infectious aerosols containing a range of opportunistic pathogens such as Mycobacterium chimaera, other non-tuberculous mycobacterial (NTM) species, Pseudomonas aeruginosa and Legionella spp. Our purpose was to determine the extent of Legionella contamination and total viable count (TVC) in HCUs and HUs and to analyze the relationship by water system design of devices of two different brands (LivaNova vs. Maquet). Methods: Legionella spp. were detected and quantified by our optimized PMA-qPCR protocol; TVCs were assessed according to ISO protocol 6222. Analyses were performed in the first sampling round and after six months of surveillance. Results: Overall, Legionella spp. was detected in 65.7% of devices. In the second sampling round, Legionella positivity rates were significantly lower in water samples from the Maquet devices compared to the LivaNova ones (27.3% vs. 61.5%). LivaNova HCUs also yielded more Legionella, and aquatic bacteria counts than Maquet in both first and second-round samples. Conclusions: We recommend that all surgical patients and staff exposed to aerosols from thermoregulatory devices should be followed up for Legionella infection and that microbiological surveillance on such devices should be conducted regularly as precautionary principle.